Question
upstudy study bank question image url

\( 1 \leftarrow \quad \begin{array}{l}\text { Multiply. } \\ (\sqrt{-36})(\sqrt{-9}) \\ (\sqrt{-36})(\sqrt{-9})=\square \text { (Simplify your answer.) }\end{array} \)

Ask by Bernard Phillips. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The simplified answer is -18.

Solution

To simplify (√(-36)) (√(-9)), first express each square root in terms of i (where i² = -1):  √(-36) = √36 × i = 6i  √(-9) = √9 × i = 3i Now multiply:  (6i)(3i) = 18i² Since i² = -1, this becomes:  18(-1) = -18 The simplified answer is -18.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve \((\sqrt{-36})(\sqrt{-9})\), we first recognize that the square root of a negative number involves imaginary numbers. We can rewrite it as: \(\sqrt{-36} = \sqrt{36} \cdot i = 6i\) \(\sqrt{-9} = \sqrt{9} \cdot i = 3i\) Now we can multiply them together: \((6i)(3i) = 18i^2\). Since \(i^2 = -1\), we can substitute that in: \(18i^2 = 18(-1) = -18\). Therefore, \((\sqrt{-36})(\sqrt{-9}) = -18\).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy